2003
DOI: 10.1128/jcm.41.3.1307-1310.2003
|View full text |Cite
|
Sign up to set email alerts
|

emmGene Distribution among Erythromycin-Resistant and -Susceptible Italian Isolates ofStreptococcus pyogenes

Abstract: The phenotypes and genetic determinants for macrolide resistance were determined for 167 erythromycinresistant Streptococcus pyogenes strains. A cMLS phenotype was shown in 18% of the erythromycin-resistant strains, while inducible resistance was apparent in 31% and the M phenotype was apparent in 50%. The emm gene type of this set of resistant isolates and that of 48 erythromycin-sensitive isolates were determined. emm2 and emm48 were recorded only in the resistant strains of the M phenotype, while approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
31
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 33 publications
11
31
3
Order By: Relevance
“…This is the first study on genotypic analysis of erythromycin resistance among the GAS strains isolated from skin and soft tissue infections showing predominance of ermB gene. The similar ermB predominance was also reported earlier from Belgium, France and Italy [20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study on genotypic analysis of erythromycin resistance among the GAS strains isolated from skin and soft tissue infections showing predominance of ermB gene. The similar ermB predominance was also reported earlier from Belgium, France and Italy [20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…Most of the emm and PFGE types detected among the prtF1-positive throat clinical GAS examined in this study have previously been found among Italian throat isolates investigated for emm (5,36) or PFGE (26) typing, respectively. In a recent German study of throat GAS, prtF1 was detected only in strains with emm12 and emm6 (2), whereas in a similar Japanese study the prevalent emm types associated with prtF1 were emm12 and emm4 (17).…”
Section: Discussionmentioning
confidence: 53%
“…The PCR M typing method described by Vitali et al (35) was used. This method, recently employed to assess the emm gene distribution among ER and ES Italian GAS (36), is directed at amplifying the N-terminal region of the emm gene with a set of 21 emm-specific oligonucleotide primers specific for emm1, emm2, emm3, emm4, emm5, emm6, emm8, emm11, emm12, emm18, emm22, emm24, emm28, emm29, emm48, emm75, emm77, emm78, emm87, emm89, and emm94.…”
Section: Methodsmentioning
confidence: 99%
“…Only strains for which data concerning both the emm type and the SmaI macrorestriction analysis by PFGE were already available (19,23) were included. The study was designed to obtain (i) data on the molecular epidemiology of vir patterns in S. pyogenes strains isolated from the oropharynx, (ii) additional insights into the contribution of prophages to the global diversification of the GAS population, and (iii) evidence on the correlation between the distribution pattern of vir genes and other classification schemes based on emm typing and SmaI macrorestriction profiling.…”
mentioning
confidence: 99%
“…Hence, all 212 strains were screened by a PCR-based method for the presence of the 16 known prophage-associated vir genes: speA, speC, speH, speI, speK, speL, speM, ssa, spd1, spd3, spd4, sdn, sda, sla, mef(A), and Tet O. Primer pairs for virulence genes were from Matsumoto et al (16), those for Tet O were from Giovanetti et al (11), and those used to detect mef(A) were from Zampaloni et al (23).…”
mentioning
confidence: 99%